Optymalny Rozkład Materiałów w Rusztach Biegunowych - Gierliński, J. (Engineering Transactions, 1974)
The papers deals with the problem of optimization of polar gridworks from the point of view of their minimum deformability under prescribed Ioads. The considerations concern systems constructed of dense, regular rod lattices formed by two families of rods. Optimization parameters are the functions which describe the distribution of structural materials. The optimization condition is written in a polar coordinate system, rotational symmetry of the problem being taken into account. An example of solution concerns an annular gridwork constructed of sandwich beams.